Design of Drip Irrigation with Smart Plug-Based Timer for Urban Agriculture at Surya Makmur Farmer Group, Mantrijeron, Yogyakarta City - Arif Umami; Ni Kadek Ema Sustia Dewi; Herdiana Anggrasari; Tri Bayu Yudha Pamungkas; Aldi Dwi Saputra (Warmadewa University Press, 2024)
Kelompok Tani (KT) Surya Makmur represents a growing community committed to urban agriculture and sustainable food production such as Chilli, Lettuce, and spinach in Yogyakarta. However, challenges related to manual irrigation practices, inconsistent watering schedules, and resource management have highlighted the need for more sophisticated irrigation methods. This study integrated a drip irrigation system with a smart plug-based timer, leveraging the power of automation to optimize water use, reduce manual labor, and ensure consistent plant hydration. The installation’s design was made using Canva editing software. The installation of the drip irrigation systems includes the construction of a water reservoir tank base, assembly of irrigation channels with PVC pipes and 16mm PE hoses, emitters, and dripper sticks, and then installation of mist sprayers in the greenhouse. In this study, the tests carried out were the actual emitter flow rate, evaporation rate, and performance tests, including the coefficient of variance (CV) and emission uniformity (EU). Based on the study's results, the coefficient of variation (CV) value of 0.04% indicates good performance. The emitter with a theoretical flow rate of 8L/hour has an actual flow rate of 8.33L/hour, conforming to the equipment specifications of 94.9%. The average evaporation in the test field was recorded at 8.13 mL/hour. This study concluded that implementing the drip irrigation system has helped KT Surya Makmur reduce labor for manual irrigation practices, maintain a consistent watering schedule, and increase resource utilization efficiency.